A review: Application of Impinging Stream Drying Process for Agricultural Products in Thailand - ตรีสุทธาชีพ ปราชญา (Srinakharinwirot University Engineering Journal, 2018)
Impinging stream drying (ISD) is technology that has been studied worldwide. In Thailand, the first publication of ISD was shown in 2007 and continuing been studied from then. This article reviewed the principle of impinging stream, and research of ISD in. Most research were focused on designing and verifying factors affected the efficiency of ISD. Testing materials are mostly agricultural products, including soy bean residue, rice paddy and parboiled rice. To assess the efficacy of ISD, volumetric water evaporation rate, volumetric heat transfer coefficient and energy consumption were determined in most research. Recent research was focusing on using ISD in rice which is a most important agricultural product in Thailand. The research was expanded to study in the field of rice’s quality. This will lead to the realistic for the application of ISD in rice production industry in the future.